2010
DOI: 10.1007/s10812-010-9341-5
|View full text |Cite
|
Sign up to set email alerts
|

Structural and optical properties of thin films of Cu(In,Ga)Se2 semiconductor compounds

Abstract: The chemical composition of Cu(In,Ga)Se 2 (CIGS) semiconductor compounds is analyzed by local x-ray spectral microanalysis and scanning Auger electron spectroscopy. X-ray diffraction analysis reveals a difference in the predominant orientation of CIGS films depending on the technological conditions under which they are grown. The chemical composition is found to have a strong effect on the shift in the self-absorption edge of CIGS compounds. It is shown that a change in the relative proportion of Ga and In in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(14 citation statements)
references
References 23 publications
2
9
0
3
Order By: Relevance
“…This localization suggests a strong preference for defect formation at, or defect/impurity segregation to, these particular grain boundary structures. The E V + 0.47 eV trap is similar to the E V + 0.41 eV level reported by Rincón et al, and Zhang et al, who suggested that it was associated with In vacancies [15], [22], [23] or Fe impurities [10]. While it is not possible to confirm or deny these attributions given the nano-DLTS data alone, it should provide valuable guidance for future nanometer-scale chemical and/or structural characterization to determine the exact physical source.…”
Section: B Characterization Of Cu(inga)se 2 With Nano-deep-level Trsupporting
confidence: 87%
See 1 more Smart Citation
“…This localization suggests a strong preference for defect formation at, or defect/impurity segregation to, these particular grain boundary structures. The E V + 0.47 eV trap is similar to the E V + 0.41 eV level reported by Rincón et al, and Zhang et al, who suggested that it was associated with In vacancies [15], [22], [23] or Fe impurities [10]. While it is not possible to confirm or deny these attributions given the nano-DLTS data alone, it should provide valuable guidance for future nanometer-scale chemical and/or structural characterization to determine the exact physical source.…”
Section: B Characterization Of Cu(inga)se 2 With Nano-deep-level Trsupporting
confidence: 87%
“…3 provides Arrhenius plots for the DLTS data revealing E V + 0.27 and E V + 0.47 eV levels with extracted average trap concentrations and cross sections given in Table I. The presence and concentration of these traps are typical of high-quality CIGS films and have previously been characterized and tentatively attributed to various sources [10], [15], [22], [23].…”
Section: A Characterization Of Cu(inga)se 2 With Conventional Deep-mentioning
confidence: 91%
“…В настоящее время тонкие пленки твердых растворов CuIn 1−x Ga x Se 2 (CIGSe) со структурой халькопирита являются одними из наиболее перспективных материалов, используемых в качестве светопоглощающих слоев солнечных элементов (СЭ) [1][2][3][4][5]. Ширина запрещенной зоны твердых растворов CIGSe в зависимости от состава 0 ≤ x ≤ 1, определяемого соотношением x ∼ Ga/(Ga + In), может изменяться в пределах E g ∼ 1.03−1.68 эВ при комнатной температуре [5,6]. Это позволяет получать материал со значением E g ∼ 1.15−1.35 эВ, приближенным к максимуму спектрального распределения солнечной энергии, обеспечивающий наибольшую эффективность фотопреобразования в СЭ с одним p−n-переходом [7].…”
Section: Introductionunclassified
“…Это позволяет получать материал со значением E g ∼ 1.15−1.35 эВ, приближенным к максимуму спектрального распределения солнечной энергии, обеспечивающий наибольшую эффективность фотопреобразования в СЭ с одним p−n-переходом [7]. Как известно, твердые растворы CIGSe являются прямозонными полупроводниками, обладающими высоким коэффициентом поглощения света α ∼ 10 5 см −1 , и поэтому светопоглощающие слои в СЭ формируются с толщиной ∼ 1−3 мкм [2,[4][5][6]. СЭ, созданные на основе твердых растворов CIGSe, обладают такими достоинствами, как незначительное падение мощности при повышении температуры, слабая чувствительность к затемнению [8], высокая радиационная стойкость [9][10][11].…”
Section: Introductionunclassified
“…The stoichiometric ratio of main chemical constituents of the CIGS absorber is known to govern its energetic and electronic properties. [15][16][17][18] reported the multi-elemental analytical characterization of different qualities of solid silicon using LIBS, in particular, the investigation of optimal environmental parameters such as the pressure and the composition of buffering gas to improve detection limit of impurities such as boron, calcium and chromium etc. and addressed the application of LIBS for solar cell industry.…”
Section: Introductionmentioning
confidence: 99%